A new technique for the reconstruction of complex portal vein anomalies in right lobe living liver donors - DEMİRBAŞ, BAHA TOLGA (My University, 2012)
Living donor liver right lobe transplantation using donors with variation of the right sectorial portal vein is considered a challenging procedure in terms of the donor\"s safety and the complexity of reconstruction in the recipient. We describe an innovative technique to reconstruct double portal vein orifices via a deceased donor iliac vein graft. The postoperative course of the recipient was uneventful. Doppler ultrasound on the fourth postoperative month revealed equivalent flow in both portal vein branches. Reconstruction of double right portal vein branches using a cryopreserved iliac vein is a valuable technique for utilizing right lobe grafts with challenging portal vein anatomy.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; GASTROENTEROLOJİ VE HEPATOLOJİ; Klinik Tıp; Klinik Tıp (MED); GASTROENTEROLOGY & HEPATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Gastroenterology; Hepatology; liver transplantation; living donor; portal vein variations; venous plasty; TRANSPLANTATION; liver transplantation; living donor; portal vein variations; venous plasty